A far red emissive RNA aptamer–fluorophore system for demethylase FTO detection: design and optimization. (23rd February 2023) - Gao, Wenjuan; Xu, Liren; Jing, Jing; Zhang, Xiaoling
Abstract : A universal strategy for demethylase detection in the far red region, relying on the affinity between an RNA aptamer and an organic fluorophore. Abstract : Fat mass and obesity-associated protein (FTO) is a demethylase that participates in N6-methyladenosine (m6A) RNA modification. This demethylase, previously linked to obesity and diabetes, is dysregulated in a number of malignancies and has either an oncogenic or a tumor-suppressive function. However, the full function of the FTO protein is still unclear due to a lack of effective analytical methods. Thus, we present the design and optimization of a "turn-on" far red fluorescent RNA aptamer–fluorophore system for FTO detection. A series of Mango RNA mutants containing N6-methyladenosine were created to weaken their binding abilities with a thiazole orange derivative (TO3-Acetate). Several advantageous nucleotides A12, A17, A22, A23, and A28 for TO3-Acetate binding were changed into m6A to increase the detection capacity. The wild type RNA aptamer can be produced with regained TO3-Acetate binding ability together with the demethylation of m6A by FTO, increasing its fluorescence brightness at 660 nm. The mutant with A22 methylation proved to be the most successful, and it benefits from a quick and sensitive response. Additionally, this approach has superior biocompatibility attributed to its far red excitation and emission in biological samples.